The phylogeny of stiletto flies (Diptera: Therevidae). (6th October 2015) - WINTERTON, SHAUN L.; HARDY, NATE B.; GAIMARI, STEPHEN D.; HAUSER, MARTIN; HILL, HILARY N.; HOLSTON, KEVIN C.; IRWIN, MICHAEL E.; LAMBKIN, CHRISTINE L.; METZ, MARK A.; TURCO, FEDERICA; WEBB, DONALD; YANG, LONGLONG; et al.
Abstract: The therevoid clade represents a group of four families (Apsilocephalidae, Evocoidae, Scenopinidae and Therevidae) of lower brachyceran Diptera in the superfamily Asiloidea. The largest of these families is that of the stiletto flies (Therevidae). A large‐scale (i.e. supermatrix) phylogeny of Therevidae is presented based on DNA sequence data from seven genetic loci (16S, 18S and 28S ribosomal DNA and four protein‐encoding genes: elongation factor 1‐alpha, triose phosphate isomerase, short‐wavelength rhodopsin and the CPSase region of carbamoyl‐phosphate synthase‐aspartate transcarbamoylase‐dihydroorotase). Results are presented from Bayesian phylogenetic analyses of approximately 8.7 kb of sequence data for 204 taxa representing all subfamilies and genus groups of Therevidae. Our results strongly support the sister‐group relationship between Therevidae and Scenopinidae, with Apsilocephalidae as sister to Evocoidae. Previous estimates of stiletto fly phylogeny based on morphology or DNA sequence data, or supertree analysis, have failed to find significant support for relationships among subfamilies. We report for the first time strong support for the placement of the subfamily Phycinae as sister to the remaining Therevidae, originating during the Mid Cretaceous. As in previous studies, the sister‐group relationship between the species‐rich subfamilies Agapophytinae and Therevinae is strongly supported. Agapophytinae are recovered as monophyletic, inclusive of the Taenogera group. Therevinae comprise the bulk of the species richness in the family and appear to be a relatively recent and rapid radiation originating in the southern hemisphere (Australia + Antarctica + South America) during the Late Cretaceous. Genus groups are defined for all subfamilies based on these results.